Northanger Abbey (Singapore Penguin Random House, 2024)
Catherine Morland is a seventeen-year-old romantic at heart, fond of reading Gothic novels. One weekend she is invited by friends to spend a season in Bath, and for the first time participates in glamorous balls unique to the nineteenth century London lifestyle. So it happens, at one ball she meets the intriguing and wealthy Henry Tilney, her over-active imagination leads her to expect dramatic twists at every turn. However, the truth turns out to be far more complicated and lot more mundane; and love happens to be a lot simpler than her novel obsessed young heart had imagined. Will the reality be a disappointment or sweet relief for her? Young Catherine goes through many self-induced trials to learn the simple lesson of life.
Keywords: Novel- English; Fiction- English